Proving Corruption Without Confession: A Theory of Evidentiary Convergence for Illicit Enrichment, Asset Disproportion, and Hidden Beneficial Ownership - H.B. Hasan Basri (Punggawa Law Review, 2026)
This article addressed the evidentiary difficulty of proving corruption in the absence of confession, explicit quid pro quo language, or formal ownership links. It proposed an evidentiary convergence approach that treated proof as the alignment of independent evidentiary tracks rather than reliance on a single decisive item. The analysis developed two substantive domains. First, illicit enrichment and asset disproportion were assessed as probative only when wealth anomalies were verified, temporally aligned with authority-linked opportunities, and reinforced by concealment indicators, while lawful explanations were tested through objective verification. Second, hidden beneficial ownership was examined through functional control markers, including decision control, economic benefit enjoyment, operational footprints, and risk-bearing patterns, allowing control to be proven even when title was displaced to nominees. The study also formulated an operational design using an evidence matrix and evaluative standards to strengthen inference while preserving fair-trial safeguards. The findings indicated that disciplined convergence improved reliability in no-confession cases without normalizing burden shifting or lifestyle-based prejudice.